Motivation, anxiety and grit: Interactive factors determining language learning success - ช่างเหล็ก, อันซอรี่; พลานุกูลวงศ์, ธัญภา (Journal of Liberal Arts Prince of Songkla University, 2017)
The study aimed at investigating the following two areas: 1) three psychological factors determining language learning success: motivation, anxiety, and grit, and 2) differences in the three factors between high and low achievement groups. One hundred and eighty Matthayom 6 students of PSU Wittayanusorn School responded to three sets of questionnaires including Learning Motivation Questionnaire, Foreign Language Classroom Anxiety Questionnaire, and Grit Scale. The statistical results showed that, overall, foreign language learning motivation was positively and significantly correlated to foreign language learning anxiety and grit. Regarding the level of achievement, the study revealed that the high and low achievers’ motivation levels were high. However, the low achievers had a significantly higher level of anxiety than the high achievers, while the high achievers had a significantly higher level of grit than the low achievers. The results implied that to achieve higher goals in learning a language, the learners should have a high level of motivation and grit, and low level of anxiety. It was suggested that language instructors create a class environment to foster motivation, reduce the degree of anxiety and enhance the personality trait of grit in learners.